Learning About Water Management through the African Catchment Game - Fox, Roddy; Rowntree, Kate; Fraenkel, L. (Investigaciones Geográficas: Una mirada desde el sur, 2013)
The African Catchment Game (ACG) is an innovative role-playing game for Geography educators that simulates a “real imaginary country”. It enables the participants to explore how rural and urban stakeholders in southern African countries may, or may not, develop scenarios of sustainable water use. The ACG has been developed from Graham Chapman’s the Green Revolution Game/Exaction of the 1970s and 1980s. Our modifications to Chapman’s game are under-pinned by theories of Complex Adaptive Systems and educational approaches based on constructivist, active/experiential learning models. This paper examines the impact of two game runs through examining the experiences of the participants and managers of the game and analyzing empirical data collected during each game run. The African Catchment Game was played twice in Finland in 2008 as part of a collaboration intended to explore the possibilities of simulations being used as tools for predicting African futures. Our analysis shows that the participants’ understanding altered and deepened as a result of playing the game. The nature of the game, as a Complex Adaptive System, and the use of a constructivist learning approach, means that the particular learning that took place cannot be extrapolated to more universal contexts, but the value of the learning process can be more generally applied.